Social determinants of health care seeking delay among newly-diagnosed symptomatic pulmonary tuberculosis patients in Cebu City, Philippines a cross-sectional study - Duavis, Mark Johnuel M. (2020)
Tuberculosis (TB) remains a major public health dilemma in the Philippines. While free and effective TB diagnosis and treatment are available since 1996, a number of patients still delay accessing them. This study was aimed at measuring the TB patient?s average health care seeking delay (HCSD) from symptom onset to presentation at the directly observed treatment short-course (DOTS) facility and identifying its significant determinants. A descriptive, analytical, correlational, cross-sectional survey was done to 127 newly-diagnosed TB patients from 10 government-owned TB DOTS facilities in Cebu City from May?July 2017. Respondents were categorically grouped into ?prompt health seekers? and ?delayed health seekers? using a 49-d norm-referenced median dichotomy. A mean HCSD of 59 d was recorded. Seventy-five percent (75%) of the respondents experienced cough. At the onset of symptoms, more than a third of them reported not having any knowledge about TB-related symptoms nor were aware of the available public TB services. Most respondents have made 2?3 prior health recourses, mostly through self-medication (51%), before finally contacting a DOTS facility. Thirty-one percent (31%) of them first contacted a private medical clinic before any other health care provider or institution. On univariate analysis, seven independent variables ? namely, marital status (p = 0.044), number of symptoms experienced (p = 0.000), type of symptom first experienced (p = 0.016), perceived dangerousness of all the symptoms experienced (p = 0.009), perceived dangerousness of the first symptom experienced (p = 0.001), perceived social stigma (p = 0.035), and perceived social support (p = 0.002) ? were found to significantly determine health-seeking delays. On multivariate analysis, the presence of marital partners (p-value 0.014) and a low level of perceived social support (p-value 0.038) are significant determinants of longer delays. With these extended delays, expanding TB interventions to include family engagement, social mobilization, and the creation of social support groups is recommended to increase the country?s TB notification rate. (Author's abstract)
Includes bibliographical references (pages 616-617)
Keywords: Health and wellness; Case detection; Health care seeking delay; Marital status; Philippines -- Social determinants of health care seeking delay among newly-diagnosed symptomatic pulmonary tuberculosis patients; Social support; Tuberculosis